2016
DOI: 10.5535/arm.2016.40.5.794
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Oroesophageal Tube Feeding via the Airway in Patients With Dysphagia

Abstract: ObjectiveTo investigate the feasibility of the use of the oropharyngeal airway (OPA) during intermittent oroesophageal tube (IOET) feeding.MethodsTen patients, who were evaluated using the videofluoroscopic swallowing study (VFSS), were enrolled. One patient withdrew from the study during the study period. Tube insertion time with and without OPA use was recorded in the same patients in a random order during the VFSS. Patients who could safely undergo IOET feeding were then randomly allocated to 2 groups (OPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…During oral intubation, the posterior pharyngeal and swallowing reflexes and promoted the recovery of swallowing function. Studies have shown that compared with continuous tube feeding, IOE tube feeding could significantly increase the rate of dysphagia function improvement by 5.22 times, increase total serum protein and serum albumin levels of stroke patients with dysphagia, and was more conducive to the conversion of patients to complete oral feeding ( 17 19 ). According to the guidelines ( 20 ), we respect the wishes of patients and allow them to participate in treatment decision-making, which may help improve their cooperation and swallowing function.…”
Section: Discussionmentioning
confidence: 99%
“…During oral intubation, the posterior pharyngeal and swallowing reflexes and promoted the recovery of swallowing function. Studies have shown that compared with continuous tube feeding, IOE tube feeding could significantly increase the rate of dysphagia function improvement by 5.22 times, increase total serum protein and serum albumin levels of stroke patients with dysphagia, and was more conducive to the conversion of patients to complete oral feeding ( 17 19 ). According to the guidelines ( 20 ), we respect the wishes of patients and allow them to participate in treatment decision-making, which may help improve their cooperation and swallowing function.…”
Section: Discussionmentioning
confidence: 99%
“…Blind insertion is related to the risk of aspiration pneumonia in unconscious patients, as the tube may be placed into the larynx or its insertion may cause torsion at the oropharyngeal level 10,33. Shin et al suggested that using the oropharyngeal airway could be helpful during OE tube feeding in patients with dysphagia 5…”
Section: Discussionmentioning
confidence: 99%
“…Acute stroke patients with severe dysphagia usually use compensatory feeding methods such as a nasogastric (NG) tube or parenteral feeding 5,6. NG tube feeding can be a proper alternative enteral feeding method; however, it is inconvenient and sometimes causes complications such as aspiration pneumonia, gastroesophageal reflux, and diarrhea 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, tube-feeding nutrition causes the throat reflex to become passive, thereby producing swallowing difficulties. To reduce these problems, intermittent tube feeding has been employed in the rehabilitation of stroke patients with dysphagia as a nutritional support and dysphagia strategy, [24,25] but its application in PED patients needs further study.…”
Section: Development Of the Ped Predictive Modelmentioning
confidence: 99%